Heterosis for yield and yield contributing traits in sunflower (Helianthus annuus L.): Heterosis for yield and yield contributing traits in sunflower (Helianthus annuus L.) - B P AILWAR; M K GHODKE; R G TATHE (Journal of Oilseeds Research, 2020)
The present experiment involved four CMS lines and six testers which were crossed in line x tester fashion to estimate the heterosis for seed yield and yield contributing traits in sunflower. Resulting 24 F1 hybrids were evaluated in two replications in RBD along with two commercial checks LSFH-171 and LSFH-35. Range of standard heterosis in 24 F1 hybrids over check LSFH-171 was from -6.42 to 31.74 and over the other check LSFH- 35 it was from -13.56 to 13.56 for oil content. Extent of heterosis for seed yield in hybrids ranged from -20.51 to 37.18 over LSFH-171 and from -6.06 to 62.12 over LSFH-35. Hybrid PET 89-1 x EC-601951 exhibited significant negative heterosis for early flowering and days to maturity over both checks. Based on per se performance, hybrids CMS 234A x EC-601957, CMS-234A x EC-601951, CMS-243A x EC-601957, PET-89-1A x EC-601951 and CMS234A x EC-623008 were superior for oil content and most of the yield contributing traits indicating them to be promising new combinations for hybrid development.